The reflection level and the construction of professional identity of university students. Issue 1 (2nd January 2021) - Engelbertink, Monique M.J.; Colomer, Jordi; Woudt- Mittendorff, Kariene M.; Alsina, Ángel; Kelders, Saskia M.; Ayllón, Sara; Westerhof, Gerben J.
ABSTRACT: To strengthen students' professional identity (PI), it is vital to give reflection a central place in higher education. The aim of this study is to determine the extent to which students reflect on five components of PI (self-image, self-esteem, task perception, job motivation and future perspective) and at what reflection level. Twenty-five reflection narratives from Spanish and Dutch students from five different study programmes were qualitatively analysed and quantitatively evaluated to find out about students' identifying and self-assessing PI components. The results indicate that PI components were clearly recognizable in the reflection reports and could be classified using one of the four levels of reflection with high inter-rater reliability. About 40% of the students achieved the critical reflection level on one or more PI components. Reflecting on the five components of PI, with the aim of achieving the level of critical reflection, can be a useful guide for students.